2021
DOI: 10.1038/s41598-021-86204-3
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the major lactate transporter of Toxoplasma gondii tachyzoites

Abstract: Toxoplasma gondii and Plasmodium falciparum parasites both extrude l-lactate, a byproduct of glycolysis. The P. falciparum Formate Nitrite Transporter, PfFNT, mediates l-lactate transport across the plasma membrane of P. falciparum parasites and has been validated as a drug target. The T. gondii genome encodes three FNTs that have been shown to transport l-lactate, and which are proposed to be the targets of several inhibitors of T. gondii proliferation. Here, we show that each of the TgFNTs localize to the T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 36 publications
0
20
2
Order By: Relevance
“…Knockdown of an uncharacterized sodium/H+ exchanger, NHE4, also showed no effect on PV pH. Several studies have identified formate-nitrite transporters (FNTs) as transporters of monocarboxylate metabolites, such as formate and lactate (27)(28)(29). FNT transport of substrates depends on the cotransport of H + , thus export of lactate or other substrates is intrinsically linked to acidification of the environment.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Knockdown of an uncharacterized sodium/H+ exchanger, NHE4, also showed no effect on PV pH. Several studies have identified formate-nitrite transporters (FNTs) as transporters of monocarboxylate metabolites, such as formate and lactate (27)(28)(29). FNT transport of substrates depends on the cotransport of H + , thus export of lactate or other substrates is intrinsically linked to acidification of the environment.…”
Section: Discussionmentioning
confidence: 99%
“…FNT transport of substrates depends on the cotransport of H + , thus export of lactate or other substrates is intrinsically linked to acidification of the environment. Previous work suggested that FNT1 is the major FNT in tachyzoites (27)(28)(29). To determine the role of FNT1 and potentially FNT2 in acidification of the PV during egress, we endogenously tagged FNT1 and FNT2 with an mNG-AIDTy cassette.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations